К познанию четырехногих клещей (Acari, Eriophyoidea) с осок Крыма - Митрофанов, В.И.; Шаронов, А.А.; Секерская, Н.П. (Вестник зоологии, 1983)
Two of five tetrapod mite species found in the Crimea on Carex are described as new: Novophytopus tauricus sp. n.— similar to N. rosiratae Roiv., differs by strong spine-like accesor chetae and by the length of ventral and lateral chetae; Eriophyes lentiginosus sp. n. differs from all Carex dwelling representatives of the genus by the absence of costulac on prodorsum and five-ray empodium.